(untitled) (Fiep Bulletin - online, 2013)
This study is an excerpt from the essay called "The School Club of Rio de Janeiro: alternative of expanding the school day." In this article we attempted to perform a historical analysis of the process of constitution of School Club of Rio de Janeiro under the Municipal Education Secretariat of Rio de Janeiro (RJ-SME), while an expansion project of school time from the perspective of leisure . For this it was necessary to conduct a focus on political issues at the time of creation, but also the historical background of the Project School Club - the CILC-Tide Project and School Sport Club - developed by the Sub-Dean for Development and Extension, Federal University of Rio de Janeiro (UFRJ), in the 1980s. The understanding of these experiences help them understand their deployment within the City Department of Education as a proposed expansion of school time.